Larangan Riba Dalam Islam Dan Dampaknya Terhadap Stabilitas Ekonomi - Holil Nawawi (Qolamuna : Jurnal Studi Islam, 2024)
The prohibition of riba constitutes a fundamental principle in Islamic economic thought, extending beyond apurely normative-religious injunction to encompass structural implications for economic stability. Thisstudy aims to examine the prohibition of riba from the perspective of fiqh muʿāmalah and to analyze itsrelevance to macroeconomic stability. Employing a normative qualitative approach, this research is based onlibrary research that analyzes primary sources, including the Qur’an and Hadith, as well as secondarysources such as classical and contemporary works on fiqh muʿāmalah, Islamic economics, and macroeconomictheory. The findings indicate that riba is conceptualized in Islamic jurisprudence as an unjust economicpractice that separates profit from risk and productive activity. From a macroeconomic perspective, interest-based systems tend to encourage excessive debt accumulation, financial speculation, and structural imbalances between the financial and real sectors, thereby increasing vulnerability to economic crises. Incontrast, the Islamic economic system, which prohibits riba and emphasizes profit-and-loss sharingmechanisms, promotes risk sharing, asset-backed financing, and stronger linkages to the real economy.This study concludes that the prohibition of riba possesses strong economic rationality and is closely alignedwith efforts to maintain macroeconomic stability and distributive justice. By integrating fiqh-based analysiswith macroeconomic theory, this research demonstrates that Islamic economic principles offer a conceptuallyviable alternative for addressing contemporary global economic instability. The study contributes to thetheoretical development of Islamic economics and provides policy-relevant insights for the advancement of amore stable and equitable financial system. Keywords: riba, Islamic economics, fiqh muʿāmalah, macroeconomic stability, risk sharing.